Empowering IDPs with SMS: A Randomized Controlled Trial in Bogota - Mariana Blanco; Juan F. Vargas (Inter-American Development Bank (IDB), 2010)
A randomized controlled trial was carried out in Bogota, home to the majority of Colombias internally displaced persons (IDPs), to assess whether the use of short message service (SMS) technology effectively informed this population of its eligibility to receive social benefits. The methodology was to randomly inform half of the sample populations households of their eligibility via SMS and estimate the Local Average Treatment Effect of the text message on the awareness of available benefits. While the findings conclude that on average treated households are more aware of their rights, a more disaggregated analysis suggests there is variation of awareness across benefit type. The analysis further suggests that the intervention was successful in empowering IDPs and indicates that the use of SMS as a policy instrument should be expanded.
Keywords: C93; 330; Internally displaced persons; Short message service; Field experiments; Colombia